Surrogate Preferences on the Physician Orders for Life-Sustaining Treatment Form. (17th May 2018) - Chen, Elizabeth E; Pu, Charles T; Bernacki, Rachelle E; Ragland, Julia; Schwartz, Jonathon H; Mutchler, Jan E
Abstract: Background and Objectives: The purpose of this study is to compare treatment preferences of patients to those of surrogates on the Physician Orders for Life-Sustaining Treatment (POLST) forms. Research Design and Methods: Data were collected from a sequential selection of 606 Massachusetts POLST (MOLST) forms at 3 hospitals, and corresponding electronic patient health records. Selections on the MOLST forms were categorized into All versus Limit Life-Sustaining Treatment. Multivariable mixed effects (grouped by clinician) logistic regression models estimated the impact of using a surrogate decision maker on choosing All Treatment, controlling for patient characteristics (age, severity of illness, sex, race/ethnicity), clinician (physician vs non-physician), and hospital (site). Results: Surrogates signed 253 of the MOLSTs (43%). A multivariable logistic regression model taking into consideration patient, clinician, and site variables showed that surrogate decision makers were 60% less likely to choose All Treatment than patients who made their own decisions (odds ratio = 0.39 [95% confidence interval = 0.24–0.65]; p < .001). This model explained 44% of the variation in the dependent variable (Pseudo- R 2 = 0.442; p < .001); mixed effects logistic regression grouped by clinician showed no difference between the models (LR test = 4.0e-13; p = 1.00). Discussion and Implications: Our study took into consideration variation at the patient, clinician, and site level, and showed that surrogates had a propensity to limit life-sustaining treatment. Surrogate decision makers are frequently needed for hospitalized patients, and nearly all states have adopted the POLST. Researchers may want study decision-making processes for patients versus surrogates when the POLST paradigm is employed.